2021
DOI: 10.3390/life11080760
|View full text |Cite|
|
Sign up to set email alerts
|

The Microbiota/Microbiome and the Gut–Brain Axis: How Much Do They Matter in Psychiatry?

Abstract: The functioning of the central nervous system (CNS) is the result of the constant integration of bidirectional messages between the brain and peripheral organs, together with their connections with the environment. Despite the anatomical separation, gut microbiota, i.e., the microorganisms colonising the gastrointestinal tract, is highly related to the CNS through the so-called “gut–brain axis”. The aim of this paper was to review and comment on the current literature on the role of the intestinal microbiota a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 207 publications
(236 reference statements)
0
6
0
5
Order By: Relevance
“…Considering that (a) the gut is the most dynamic immunological environment in the body, (b) gut microbiome colonisation early in life is critical for the optimal development of the immune system [39], and (c) that dysbiosis of the intestinal ecosystem may affect immune responses [40], dysfunctions such as chronic inflammation and oxidative stress, which have been implicated in schizophrenia, are proposed to be, at least in part, associated with changes in the microbiome [14]. These include the microbiome's mediation in the regulation of pro-inflammatory cytokines, which may, in turn, influence the pathophysiology of mental disorders [16]; for example, increased IL-6, IL-1β and IL-2R concentrations are reported in chronic schizophrenic patients [41].…”
Section: Pathophysiological Mechanismsmentioning
confidence: 99%
“…Considering that (a) the gut is the most dynamic immunological environment in the body, (b) gut microbiome colonisation early in life is critical for the optimal development of the immune system [39], and (c) that dysbiosis of the intestinal ecosystem may affect immune responses [40], dysfunctions such as chronic inflammation and oxidative stress, which have been implicated in schizophrenia, are proposed to be, at least in part, associated with changes in the microbiome [14]. These include the microbiome's mediation in the regulation of pro-inflammatory cytokines, which may, in turn, influence the pathophysiology of mental disorders [16]; for example, increased IL-6, IL-1β and IL-2R concentrations are reported in chronic schizophrenic patients [41].…”
Section: Pathophysiological Mechanismsmentioning
confidence: 99%
“…In addition, the functional enrichment analysis of 16S rRNA profile suggested that SMPS intervention affected biological metabolism (including starch and sucrose metabolism, biosynthesis of amino acids, galactose metabolism and other glycan degradation pathways) through regulating intestinal flora. Interestingly, the recent literature indicated that the gut microbiota had effect on brain functions through endocrine and metabolic pathways and the enteric network, especially in the onset and maintenance of neurodevelopment and neurodegenerative disorders (Marazziti et al, 2021). ASD is a neurodevelopmental disease.…”
Section: Discussionmentioning
confidence: 99%
“…The GM is a diverse and dynamic microbes’ population with extensive and essential interactions with the digestive, immune, and nervous systems ( Huo et al., 2017 ; Marazziti et al., 2021 ). The complex bidirectional communication systems between the GI tract and the brain were initially termed “gut-brain axis” and then renamed “microbiota-gut-brain axis”, considering the pivotal role of GM in sustaining local and systemic homeostasis ( Lavelle and Sokol, 2020 ; Banfi et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%